2001
DOI: 10.1161/hc4701.100513
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Metabolite 1-Palmitoyl-Lysophosphatidylcholine Enhances Human Ether-a-Go-Go -Related Gene (HERG) K + Channel Function

Abstract: Background-Lysophosphatidylcholine (LPC), a naturally occurring phospholipid metabolite, accumulates in the ischemic heart and causes extracellular K ϩ accumulation and action potential shortening. LPC has been incriminated as a biochemical trigger of lethal cardiac arrhythmias, but the underlying mechanisms remain poorly understood. Methods and Results-We studied the effect of 1-palmitoyl-LPC (Pal-LPC) on currents resulting from human ether-a-go-go-related gene (HERG) expression in human embryonic kidney (HEK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 25 publications
3
27
1
Order By: Relevance
“…The addition of I HERG to this list appears to be expected as a related inwardly rectifying potassium current of lactotrophs and neuroblastoma cells is also inhibited by ceramide (Wu et al, 2001). The inhibitory mechanism of ceramide on the I K(IR) of GH 3 lactotrophs was unresolved and disparities exist though from our present findings, or those of Wang et al (Wang et al, 2001). Specifically a robust inhibition within one minute of ceramide application (~70% with 10 M C 2 ) was shown and a +10 mV shift of the activation curve (Wu et al, 2001).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The addition of I HERG to this list appears to be expected as a related inwardly rectifying potassium current of lactotrophs and neuroblastoma cells is also inhibited by ceramide (Wu et al, 2001). The inhibitory mechanism of ceramide on the I K(IR) of GH 3 lactotrophs was unresolved and disparities exist though from our present findings, or those of Wang et al (Wang et al, 2001). Specifically a robust inhibition within one minute of ceramide application (~70% with 10 M C 2 ) was shown and a +10 mV shift of the activation curve (Wu et al, 2001).…”
Section: Discussioncontrasting
confidence: 81%
“…These differences probably emanate from the cellular systems used, where such contributing factors could include heterogeneous ERG current properties owing to the presence of non-cardiac ERG family member subunits (Schäfer et al, 1999;Wimmers et al, 2002), and diversity of signalling (Barros et al, 1998;Schäfer et al, 1999). However, using HEK293 cells stably expressing HERG, as here, Wang et al (Wang et al, 2001) observed that ceramide had no significant effects on I HERG . The reason for this discrepancy is presently not known, but may arise from the time-dependent nature of the effect evident here, and from differences in the concentration of ceramide used.…”
Section: Discussionmentioning
confidence: 82%
“…Whole-cell Patch Clamp Recording-Patch clamp techniques have been described in detail elsewhere (13)(14)(15)(16). Experiments were conducted at 36 Ϯ 1°C.…”
Section: Methodsmentioning
confidence: 99%
“…Whole-cell Patch Clamp Recording-Patch clamp techniques have been described in detail elsewhere (15)(16). Currents were recorded with whole-cell voltage clamp with an Axopatch-200B amplifier (Axon Instruments).…”
Section: Methodsmentioning
confidence: 99%